Glosa krytyczna do postanowienia Naczelnego Sądu Administracyjnego z 10 lipca 2025 r., sygn. akt II GSK 432/25 - Cheba, Jakub (Studia Prawa Publicznego, 2025)
This commentary concerns the resolution of the Supreme Administrative Court of 10 July 2025, file reference II GSK 432/25, which specifically addresses the legal nature of the Prime Minister’s countersignature granted in relation to official acts issued by the President of the Republic of Poland. The Supreme Administrative Court wrongly found, a limine, that it is an act subject to administrative court review, and therefore the complaint in this regard is admissible. Adopting the above position has fa-reaching consequences, namely the possibility of discontinuing administrative court proceedings pursuant to Article 161 § 1 item 3 of the Law on Administrative Court Procedure, withdrawing the previously granted countersignature pursuant to Article 54 § 3 of the Law on Administrative Court Procedure, and granting the Prime Minister the status of a public administration body in this respect. This ruling, in the opinion of the author of the commentary, may lead to an imbalance in the activities of the President of the Republic of Poland and the Council of Ministers in the broadly understood executive and an increase in the state of legal and political uncertainty when issuing official acts requiring the signature of the Prime Minister.